MENGUNGKAP LABIRIN KEBIASAAN: STUDI KUALITATIF TENTANG BIAS DALAM ADMINISTRASI PAJAK DI INDONESIA - Donal, Endri; Putri, Anne (JURSIMA, 2024)
Indonesia's tax system, a complex labyrinth of regulations and procedures, underpins the nation's revenue collection. Yet, beneath the veneer of numerical analysis and audits lies a critical, often overlooked element: human judgment. This study delves into the under-researched area of how human biases and cognitive limitations influence risk assessment and enforcement decisions within Indonesia's Directorate General of Taxation (DJP). Cognitive biases such as confirmation bias and anchoring, coupled with cognitive limitations like bounded rationality, can significantly distort risk assessments and enforcement outcomes in tax administration. These biases not only compromise the integrity of the tax system but also erode taxpayer compliance and public trust. Consequently, Indonesia's tax ratio remains notably lower than its target, with cognitive biases contributing significantly to this shortfall. This research aims to shed light on the intersection of human judgment and tax administration in Indonesia. By examining specific biases prevalent within the DJP, this study seeks to identify practical solutions to mitigate their impact. Through in-depth interviews with tax officials, this research will provide qualitative data to understand the nuanced complexities of decision-making within the system. Ultimately, this study seeks to contribute to a more equitable and effective tax administration system in Indonesia